Defend Dissent - Borradaile, Glencora (Open textbook library., 2021)
Defend Dissent is an introduction to cryptography paired with the social impacts of surveillance and the protective potential of encryption, with a focus on US social movements. Each chapter ends with a story that brings social context to the material—from surveillance used against contemporary US protests to the African National Congress’s use of partially manual encryption in fighting apartheid in South Africa in the 80s.This book can be read linearly, or you can pick and choose what you would like to learn about. Each chapter is prefaced with what you should read first (for background) and concludes with what you might want to read next.